2022
DOI: 10.3390/ijerph192114457
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Acute Coronary Syndrome Mortality in Serbia in 2005–2019: An Age–Period–Cohort Analysis Using Data from the Serbian Acute Coronary Syndrome Registry (RAACS)

Abstract: Background: Cardiovascular diseases ranked first in terms of the number of deaths in Serbia in 2019, with 52,663 deaths. One fifth of those were from ischemic heart disease (IHD), and half of IHD deaths were from acute coronary syndrome (ACS). We present the ACS mortality time trend in Serbia during a 15-year period using the latest available data, excluding the COVID-19 pandemic. Methods: The data on patients who died of ACS in the period from 2005 to 2019 were obtained from the National Statistics Office and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Telemedicine platforms can be used to provide training content to healthcare providers (45,46). One field where this would be beneficial is interventional cardiology/radiology; recent studies in Serbia reported a limited number of trained interventional cardiologists to be an obstacle for pPCI (47,48).…”
Section: Telemedicinementioning
confidence: 99%
“…Telemedicine platforms can be used to provide training content to healthcare providers (45,46). One field where this would be beneficial is interventional cardiology/radiology; recent studies in Serbia reported a limited number of trained interventional cardiologists to be an obstacle for pPCI (47,48).…”
Section: Telemedicinementioning
confidence: 99%
“…Despite major advances in the prevention and treatment of atherosclerosis, the incidence of coronary artery disease (CAD) is increasing in many regions of the world and is starting at an earlier age [ 1 , 2 , 3 , 4 ]. A significant percentage of younger patients with acute myocardial infarction (AMI) have premature CAD [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, according to the 2017-year statistics, CVD accounted for 45% and 37% of all deaths in Europe and European Union, respectively [ 4 ]. According to a recent study, in 2019 CVD represented the major cause of death in Serbia accounting for 51.8%, while 17.7% died from ischemic heart disease [ 5 ]. Considering that cardiovascular diseases are the main cause of morbidity and mortality in their country, the Libyan Cardiac Society recently recommended that cardiovascular diseases should be given high priority in the health system to develop a program for efficient prevention, early diagnosis, and treatment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%